Identification of The Structure of The Subsurface Layer Using The Seismic Refraction Method in Nagari Malampah - Ega Zuhara (Journal of Experimental and Applied Physics, 2026)
The frequent landslides in Nagari Malampah are caused by the location of the area near an active fault zone and the effects of the 2022 earthquake centered in Pasaman Barat Regency. The study aims to identify subsurface layer structures related to landslide susceptibility using the seismic refraction method. Field data were acquired along three survey line and processed using the Time-Term Inversion method. The results indicate the presence of two main subsurface layers. The first layer exhibits P-wave velocities ranging from 277.45 to 581.85 m/s at depths of approximately 3-6 m, interpreted as unconsolidated alluvial deposits consisting of sand, slit, and clay. The second layer shows higher velocities ranging from 499.49 to 1093.12 m/s at depths of 12-32 m, suggesting denser materials such as compact clay, dense sand, and weathered bedrock. The significant velocity contrast between these layers indicates the presence of potential weak zones that may act as slip surfaces under conditions of high rainfall and seismic activity. These findings provide important information for landslide hazard assessment and mitigation planning in Nagari Malampah.